A rAAV2‐producing yeast screening model to identify host proteins enhancing rAAV DNA replication and vector yield. (22nd October 2018) - Aponte‐Ubillus, Juan Jose; Barajas, Daniel; Peltier, Joseph; Bardliving, Cameron; Shamlou, Parviz; Gold, Daniel
Abstract : Recombinant adeno‐associated viral vectors (rAAV) are promising therapies for genetic diseases. Although current platforms for recombinant vector production can generate drug material for pre‐clinical and clinical studies, rAAV biomanufacturing will eventually face commercial supply challenges if per cell vector productivity and process scalability are not improved. Because considerable efforts have traditionally focused on optimizing rAAV plasmid design, herein we investigate the impact of host cell proteins on vector production to identify proteins that may enhance rAAV yield. Using a rAAV2‐GFP‐producing Saccharomyces cerevisiae model in combination with the yeast Tet Hughes Collection screening library, we identified 22 gene candidates that improved rAAV DNA replication (rAAV‐GFP/18s rDNA ratio) and vector yield (benzonase‐resistant rAAV DNA vector genome titer) as high as 6‐fold and 15‐fold relative to control, respectively. The candidate proteins participate in biological processes such as DNA replication, ribosome biogenesis, and RNA and protein processing. The best five candidates ( PRE4, HEM4, TOP2, GPN3, and SDO1 ) were further screened by generating overexpression mutants in the YPH500 yeast strain. Subsequent clone evaluation was performed to confirm the rAAV‐promoting activity of selected candidates under plate‐based and bioreactor‐controlled fermentation conditions. Digital droplet PCR analysis of cell lysate and AVB resin‐purified material confirmed HEM4 and TOP2 overexpression mutants displayed the highest per cell total rAAV DNA productivity (1.6 and 1.7‐fold increase over control, respectively) and per cell vector productivity (3 and 4‐fold over control, respectively). This evaluation confirmed that overexpression of HEM4 and TOP2 proteins enhanced total and benzonase‐resistant rAAV DNA yield. Further studies are needed to understand their mechanism of action and to assess their potential application in molecular strategies for rAAV production. © 2018 American Institute of Chemical Engineers Biotechnol. Prog ., 35: e2725, 2019